225k views
5 votes
If cos 0 = 3/radical 22 and angle 0 is in Quadrant I, what is the exact value of tan 20 in

simplest radical form?

If cos 0 = 3/radical 22 and angle 0 is in Quadrant I, what is the exact value of tan-example-1
User Jeand
by
5.0k points

1 Answer

2 votes

Answer:


  • \tan2\theta =-(3√(13))/(2)

Explanation:

To find:-

  • The value of
    \tan2\theta .

Answer:-

We are here given that the value of,


\longrightarrow \cos\theta=(3)/(√(22)) \\

And we know that cosine is the ratio of base and hypotenuse. Therefore,


\longrightarrow \cos\theta =(b)/(h) \\

So we can also say that,


\longrightarrow \cos\theta = (b)/(h)=(3)/(√(22))\\

Let us take the given ratio to be 3x:22x . Now we may find out the value of perpendicular using Pythagoras theorem . The Pythagoras theorem is ,

Pythagoras theorem:-

  • In a right angled triangle the sum of squares of perpendicular and base is equal to the square of hypotenuse.

Mathematically,


\longrightarrow \boxed{ \boldsymbol{p^2+b^2=h^2}} \\

where the symbols have their usual meaning.

On substituting the respective values, we have;


\longrightarrow p^2+(3x)^2=(√(22)x)^2 \\


\longrightarrow p^2 = 22x^2-9x^2\\


\longrightarrow p^2=13x^2 \\


\longrightarrow \boldsymbol{ p = √(13)x} \\

Now again , we know that, tangent is defined as the ratio of perpendicular and base. Therefore,


\longrightarrow \tan\theta = (p)/(b) \\


\longrightarrow \tan\theta = (√(13)x)/(3x)\\


\longrightarrow \boldsymbol{ \tan\theta = (√(13))/(3)}\\

Now we may use a identity which is ,


\longrightarrow\boxed{ \boldsymbol{ \tan (2x)= (2\tan x)/(1-\tan^2 x)}}\\

On substituting the respective values, we have;


\longrightarrow \tan2\theta = ( 2\tan\theta)/(1- \tan^2\theta)\\


\longrightarrow \tan2\theta = (2\bigg((√(13))/(3)\bigg))/(1-\bigg((√(13))/(3)\bigg)^2 ) \\


\longrightarrow \tan2\theta = ((2√(13))/(3))/(1-(13)/(9)) \\


\longrightarrow \tan2\theta = ((2√(13))/(3))/((9-13)/(9)) \\


\longrightarrow \tan2\theta = ((2√(13))/(3))/((-4)/(9)) \\


\longrightarrow \tan2\theta = -(2√(13)\cdot 9)/(3\cdot 4 ) \\


\longrightarrow \boxed{\boldsymbol{ \tan2\theta = -(3√(13))/(2)}} \\

This is the required answer .

User Oliver K
by
4.6k points